2020
DOI: 10.3390/app10020602
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Earthquake-Induced Building Destruction from Space Using a Pretrained CNN Model

Abstract: The building is an indispensable part of human life which provides a place for people to live, study, work, and engage in various cultural and social activities. People are exposed to earthquakes, and damaged buildings caused by earthquakes are one of the main threats. It is essential to retrieve the detailed information of affected buildings after earthquakes. Very high-resolution satellite imagery plays a key role in retrieving building damage information since it captures imagery quickly and effectively aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…To know if the model indeed shows this behavior, the performance of all classes should be analyzed separately. Only two studies reported this, and in both cases the model performed better on the majority class (not destroyed) than on the minority (destroyed) class [32,45], suggesting that a larger class imbalance can lead to better accuracy while not indicating a better predictive value.…”
Section: Previous Researchmentioning
confidence: 96%
See 4 more Smart Citations
“…To know if the model indeed shows this behavior, the performance of all classes should be analyzed separately. Only two studies reported this, and in both cases the model performed better on the majority class (not destroyed) than on the minority (destroyed) class [32,45], suggesting that a larger class imbalance can lead to better accuracy while not indicating a better predictive value.…”
Section: Previous Researchmentioning
confidence: 96%
“…Combined they covered three types: earthquake, tsunami, and hurricane, where earthquake is the most common type. Among all studies shown in Table 1, those focusing on earthquakes [13,32,37,44,45] reported the lowest performance. However, since all models have only been tested on one hazard type, it should be further researched if and how the disaster type influences the performance.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations